Effect of antitumor drugs in low concentrations on the biological, immunophenotypic and cytogenetic characteristics of human colon cancer cells in vitro - Bezdieniezhnykh, N.; Kovalova, O.; Lykhova, O.; Kocherga, R.; Vorontsova, A.; Zhylchuk, V.; Maksimyak, G.; Kudryavets, Yu. (Experimental Oncology, 2017)
Objective: To estimate the impact of the low-dose anticancer drugs (ACD) with the different mechanisms of action and human interferon (IFN) alpha 2b on the biological properties, immunophenotypic and cytogenetic characteristics of colon cancer cells in vitro. Materials and Methods: The study was performed on human colon cancer cell lines COLO 205, HT-29 and 3C-P treated with ACD and IFN in subtoxic concentrations. Expression of CD44, N-cadherin, vimentin, β-catenin, ERCC1 and Slug was assessed by immunocytochemical method. Using cytogenetic analysis, the numbers of mitoses, cells with micronuclei, apoptotic cells and cells with nuclear protrusions were studied. Results: The prolonged exposure (up to 30 days) of colon cancer cells to low-dose ACD (0.2–0.5 µg/ml cisplatin and 0.1–0.2 µg/ml irinotecan) in combination with IFN (500–1000 IU/ml) led to 37-fold decreased colony-forming activity of these cell and 10-fold reduction of the number of cells expressing mesenchymal protein markers (N-cadherin, vimentin). Also, in COLO 205 cells treated with ACD and IFN the number of SLUG- and CD44-positive cells decreased by 92 and by 85%, respectively. Long-term cultivation of HT-29 cells in the presence of cisplatin and IFN resulted in 5-fold suppression of ERCC1 expression. The cytogenetic analysis has shown that the ACD, IFN and their combinations in subtoxic concentrations caused significant genotoxic effect, suppression of cell proliferation and accumulation of cells with micronuclei. The sensitivity of colon cancer cells to ACD in standard cytotoxic concentrations did not change after prolonged low-dose exposure. Conclusion: The data showed that the prolonged action of the low doses of ACD on human colon cancer cells resulted in the suppression of cell proliferation, colony-forming activity in soft agar, expression of epithelialmesenchymal transition-associated markers and significant cytogenetic changes.